FACTORS INFLUENCING DISSEMINATION OF CREDIT INFORMATION BY CREDIT REFERENCE BUREAUS IN KENYA - KAHINDI, SAMUEL FURAHA; KAPLELACH, MR SAMSON (Journal of Public Policy and Administration, 2016)
Purpose: The purpose of this study was to analyze the factors influencing dissemination of credit information by credit reference bureaus in Kenya. Methodology: The study used descriptive survey research design. This study used primary data which was collected through use of Questionnaires. The target populations of the study were all licensed Credit Reference Bureaus in Kenya. Data from the questionnaires were analyzed using Statistical Packages for Social Sciences (SPSS) to derive descriptive results. The results found were then presented in frequency tables, bar graphs and pie charts. Results: The findings implied that macro-economic factors affect credit dissemination. Results indicated that privacy protection of credit information was one of the factors emphasized by credit bureaus. Results indicated that competition also led to low dissemination of information. The findings agreed that business ethics was one of the factor emphasize by credit bureaus. The findings also indicated there was a need by credit bureaus to appraise borrowers. Unique contribution to theory, practice and policy: The study recommended management of credit bureaus to be on the outlook and follow the trends in the technology and demand in the market so as to improve on credit dissemination and by extension that of the overall company. The study also recommended that the Government institute adequate legal and institutional measures to protect consumer information, the government should also set rules on stiff competition in the financial sectors in Kenya, the study also recommended that banks should use CRB reports to appraise borrowers and to enhance business ethics.